Evaluation of Dopamine Receptor Integrity after Sevofl urane Exposure in Neonatal Rat Brain Using Positron Emission Tomography - Qi Yin; Merle G. Paule; Tucker A. Patterson; Fang Liu; Charles M. Fogle; Scott M. Apana; Marc Berridge; William Slikker Jr; Cheng Wang; Xuan Zhang (Global Journal of Anesthesiology - Peertechz Publications, 2018)
Aims: The volatile general anesthetic sevofl urane is commonly used across all ages in the clinic. Sevofl urane-induced neurotoxic effects on the developing dopaminergic system are still unclear. The aim of this study was to evaluate the integrity of the D2/D3 receptor in developing rat brain utilizing molecular imaging techniques.  Method: Positron Emission Tomography (PET) coupled with Computerized Tomography (CT) approaches were used to evaluate the effects of developmental sevofl urane exposure on D2/D3 receptors in rat pups. The PET radiotracer, [18F]-fallypride, was used to examine whether dopamine receptors were affected by prolonged sevofl urane-exposure during the brain growth spurt. Six postnatal day (PND) 7 rats in the experimental group were exposed to sevofl urane at the clinically-relevant concentration of 2.5% (v/v) for 8 hours, and an equal number of control animals were exposed to room air for 8 hours. MicroPET/CT scans were sequentially collected on PNDs 14, 21, 28, and 35. Results: No signifi cant differences in the retention of [18F]-fallypride in striatum were detected between sevofl urane-exposed and control animals at any of the scan times. D2/D3 receptors are not affected by prolonged sevofl urane-induced general anesthesia during development. Conclusions: Sevofl urane-induced neurotoxicity in the developing rodent brain was not associated with apparent derangements in dopamine D2/D3 receptors.